ABLB - a test for functional hearing loss - MN, Vyasa Murthy (Journal of All India Institute of Speech and Hearing, 1972)
The Alternate Binaural Loudness-Balance (ABLB) test is used as a test for assessing recruitment-an abnormal growth of loudness with increase in intensity of sound. However, it appears that the test can be used to identify unilateral functional hearing loss. Here, an attempt is made to explain how this test could be used as a test for unilateral functional hearing loss